Reverse-flow reactor concept for combined SO2 and CO-oxidation in smelter off-gases; Chemical Engineering Journal; Vol. 238: Proceedings of the XX International conference on Chemical Reactors CHEMREACTOR-20 - Zagoruiko A. N. Andrey Nikolaevich (2014, 2014)
Title screen